Association Between Screen Time and Lifestyle Parameters with Executive Functions in Chilean Children and Adolescents: Potential Mediating Role of Health-Related Quality of Life - Felipe Caamaño-Navarrete; Carlos Arriagada-Hernández; Lorena Jara-Tomckowiack; Jordan Hernandez-Martinez; Pablo Valdés-Badilla; Guido Contreras-Díaz; Indya del-Cuerpo; Pedro Delgado-Floody (Children)
Background/Objective: This study aimed to (i) investigate the association between lifestyle parameters (i.e., screen time [ST], food habits, and physical activity [PA]) and health-related quality of life (HRQoL) with executive functions (EFs, i.e., attention, inhibition, working memory, and cognitive flexibility) in Chilean children and adolescents, and (ii) determine the potential mediating role of HRQoL in the relationship between ST and EFs. Methods: A total of 511 children and adolescents (51.3% female) aged 10–17 years participated. Lifestyle parameters and EFs were evaluated. Results: Attention was inversely associated with ST (β = −19.51, p < 0.001) and positively associated with HRQoL (β = 4.17, p < 0.001). Inhibition was negatively linked to ST (β = −25.17, p < 0.001) and positively associated with HRQoL (β = 3.23, p = 0.041). Working memory was inversely related to ST (β = −28.89, p = 0.001) and positively associated with PA (β = 34.01, p < 0.001) and HRQoL (β = 4.22, p = 0.003). Cognitive flexibility was associated with ST (β = −26.76, p = 0.001), PA (β = 23.23, p = 0.047), and HRQoL (β = 4.91, p = 0.004). The indirect effect confirmed that HRQoL partially mediated the relationship between ST and EFs, including attention (5%), inhibition (3.18%), working memory (3.82%), and cognitive flexibility (5.3%). Conclusions: ST was inversely associated with all EFs assessed, and HRQoL showed a potential mediating role in these relationships.